Blood, Sweat, and Fear : Violence at Work in the North American Auto Industry, 1960-80 - Milloy, Jeremy, 1979- (Book collections on Project MUSE., 2017)
"Going postal. We hear the chilling phrase and think of the rogue employee who snaps. But Blood, Sweat, and Fear shows that on-the-job bloodshed never occurs in isolation. Using violence as a lens, Jeremy Milloy provides fresh insights into the everyday workings of capitalism, class conflict, race, and gender in the United States and Canada. The result is a study that reveals the workplace as a battleground--one that saw a late-century paradigm shift from the collective violence of strikes and riots to the individualized violence of assaults and shootings. Explosive and original, Blood, Sweat, and Fear brings historical perspective to contemporary debates about North American workplace violence."--Back cover